Managerial compensation and the debt placement decision - Albring, Susan M.; Khurana, Inder K.; Nejadmalayeri, Ali; Pereira, Raynolde (Journal of Corporate Finance, 2011)
Extant research argues that borrowing from financial intermediaries subjects managers to external monitoring. However, given managers' flexibility in choosing the type of debt financing, why would managers submit themselves to external monitoring? Recent theory points to the role of managerial incentive compensation. Specifically, it is argued that managers will borrow from financial intermediaries if their compensation is tied to firm performance. Additionally, it is noted that a more optimal compensation scheme will induce managers to undertake intermediated loans only when the firm is sufficiently profitable. Such a compensation scheme is likely to exist in opaque firm settings where borrowing from financial intermediaries can serve to signal firm profitability. Our study provides corroborative evidence. We find that the choice of syndicated bank loans is positively associated with CEO equity incentives. Second, this syndicated debt-incentive compensation link is influenced by firm profitability, particularly among information problematic firms. Overall, our study points to the role of incentive compensation in the debt placement decision.